2016
DOI: 10.1007/s12031-016-0724-9
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Remote Ischemic Perconditioning and Cerebral Ischemic Postconditioning Inhibits Autophagy to Attenuate Plasma HMGB1 and Induce Neuroprotection Against Stroke in Rat

Abstract: Remote ischemic perconditioning (RIPerC) and ischemic postconditioning (IPOC) are well-acknowledged neuroprotective procedures during ischemic injury. The present study established a combined RIPerC and IPOC (RIPerC + IPOC) model in rats and studied how it would regulate the autophagy process and affect HMGB1 levels in a rat model of middle cerebral artery occlusion (MCAO). Rats with MCAO were treated with RIPerC by fastening and release of the left hind limb to achieve 4 cycles of 5 min remote ischemia reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…IPOC was also demonstrated to reduce the translocation of HMGB1 from the nucleus to the cytoplasm, and that the autophagy inhibition effect of IPOC may be caused by reduced interaction between HMGB1 and Beclin1. These results are consistent with the findings of our previous study (35), which confirmed that IPOC decreased the translocation of HMGB1 from the nucleus to the cytoplasm to exert its autophagy inhibition effect in an in vivo model of focal cerebral ischemia and IPOC. The current study adds further evidence for the mechanism of HMGB1-induced autophagy in ischemic stroke and IPOC.…”
Section: Discussionsupporting
confidence: 93%
“…IPOC was also demonstrated to reduce the translocation of HMGB1 from the nucleus to the cytoplasm, and that the autophagy inhibition effect of IPOC may be caused by reduced interaction between HMGB1 and Beclin1. These results are consistent with the findings of our previous study (35), which confirmed that IPOC decreased the translocation of HMGB1 from the nucleus to the cytoplasm to exert its autophagy inhibition effect in an in vivo model of focal cerebral ischemia and IPOC. The current study adds further evidence for the mechanism of HMGB1-induced autophagy in ischemic stroke and IPOC.…”
Section: Discussionsupporting
confidence: 93%
“…They were able to ascertain that RIC was able to induce pro-autophagy signaling. Wang et al, in SD rat models, was able to show that RIC attenuated plasma HMGB1 levels and exerted a neuroprotective effect by inhibiting the autophagy process ( 51 ).…”
Section: Mechanisms Of Limb Remote Ischemic Pre- Per- and Postcondimentioning
confidence: 99%
“…These findings imply that autophagy exerts a pivotal function in RIC-induced neuroprotection with the possible involvement of AKT/GSK3β, AMPK, and mTOR/p70S6K signaling pathways, and AKT-dependent Bcl-2 phosphorylation. However, in contrast, studies also demonstrated that inhibition of the autophagy process contributed to the protection against cerebral ischemia injury in rats subjected with ischemic post-conditioning alone or combined with RIC [ 134 , 135 ]. The potential function of autophagy in RIC-induced protection needs to be further elucidated.…”
Section: Resultsmentioning
confidence: 99%